Plasmonic Metasurfaces Situated on Ultrathin Carbon Nanomembranes - Sirmaci, Yunus Denizhan; Tang, Zian; Fasold, Stefan; Neumann, Christof; Pertsch, Thomas; Turchanin, Andrey; Staude, Isabelle (ACS Photonics, 2020)
During the past decade, optical metasurfaces consisting of designed nanoresonators arranged in a planar fashion were successfully demonstrated to allow for the realization of a large variety of flat optical components. However, in common implementations of metasurfaces and metasurface-based devices, their flat nature is thwarted by the presence of a substrate of macroscopic thickness, which is needed to mechanically support the individual nanoresonators. Here, we demonstrate that carbon nanomembranes (CNMs) having nanoscale thicknesses can be used as a basis for arranging an array of plasmonic nanoresonators into a metamembrane, allowing for the realization of genuinely flat optical devices. CNMs belong to the family of two-dimensional materials, and their thicknesses and mechanical, chemical, and electrical properties can be tailored by the choice of the molecular precursors used for their fabrication. We experimentally fabricate gold split-ring-resonator (SRR) metasurfaces on top of a free-standing CNM, which has a thickness of only about 1 nm and shows a negligible interaction with the incident light field. For optical characterization of the fabricated SRR CNM metasurfaces, we perform linear-optical transmittance spectroscopy, revealing the typical resonance structure of an SRR metasurface. Furthermore, numerical calculations assuming free-standing SRR arrays are in good overall agreement with corresponding experimental transmittance spectra. We believe that our scheme offers a versatile solution for the realization of ultrathin, ultra lightweight metadevices, and may initiate various future research directions and applications including complex sensor technologies, conformal coating of complex topographies with functional metasurfaces, fast prototyping of multilayer metasurfaces, and studying the optical properties of effectively free-standing nanoparticles without the need for levitation schemes.
CRIS-Team Scopus Importer:2023-04-20
Keywords: carbon nanomembranes; flat-optics; metasurfaces; nanoplasmonics; two-dimensional materials